Coexistence of blaOXA-48, blaVIM, and blaSHV genes in Klebsiella pneumoniae and Escherichia coli isolated from urinary tract infections: Microbiological and epidemiological analysis - Manar Abdallah; Soliman Haroun; Amin Tahoun; Yamen Mohammed Hegazy; Ramadan Eldomany (Journal of the Pakistan Medical Association, 2023)
Objective: To investigate antimicrobial resistance mechanisms of isolated bacterial strains, and their correlation with virulence profile. Method: The cross-sectional study was conducted in January 2020 at outpatient health centres in Kafrelsheikh Governorate of Egypt, and comprised urine samples from patients regardless of age and gender. Midstream samples were collected into sterile swaps which were kept in ice-cooled boxes until transported to the laboratory within 5h. Antimicrobial resistance profile of the isolated Enterobacteriaceae was done using Kirby–Bauer disk diffusion method and was confirmed with Vitek compact 2. The phenotypic of carbapenemases and extended-spectrum beta lactamase was determined, and polymerase chain reaction was used, as appropriate. Data was analysed using SPSS 20. Results: Of the 199 patients, 101(50.7%) were females and 98(49.3%) were males. The majority 73(36.6%) were aged 30-50 years. Urinary tract infection was found in 68(34.2%) patients. In 28(41.2%) of these patients, there were 32 isolates of Enterobacterales; 21(65.62%) Klebsiella pneumoniae, 7(21.87%) Escherichia coli and 4(12.5%) Enterobacter cloacae. Of the 28(41.2%) patients, 24(85.7%) were infected with a single strain; 17(70.8%) Klebsiella pneumoniae, 4(16.7%) Escherichia coli and 3(12.5%) Enterobacter cloacae. In 3(10.7%) cases, there was co-infection with Escherichia coli and Klebsiella pneumoniae, and 1(3.6%) sample had mixed infection with Klebsiella pneumoniae and Enterobacter cloacae. The other 40(58.8%) patients had other causative agents. Housewives, agricultural workers and those aged >50 years had a higher risk of urinary tract infections (p<0.05) Among Klebsiella pneumonia isolates, 6(28.5%) possessed carbapenemase-related genes and 4(19.1%) extended-spectrum beta lactamase-related genes. The carbapenemaserelated genes were bla-Verona integron-encoded metallo beta lactamase 6(100%) bla-New Delhi metallo beta lactamase-1 4(66.6%) and bla-oxacillinase-48 2(33.3%). The 4(19.1%) cases of extended-spectrum beta lactamaserelated genes had bla-temoneira gene 3(75%) and bla-sulfhydryl variable gene 4(100%). In Escherichia coli isolates, bla-oxacillinase-48 and bla-Cefotaximase genes were observed in 2(28.5%) cases. Virulence genes uridine diphosphateglucose 4-epimerase, fimbrial adhesion and mannose-resistance adhesin of Klebsiella spp genes in Klebsiella pneumoniae isolates were positive in in 16(76.2%), 14(66.7%) and 10(47.6%) cases, respectively. All 21(100%) isolates of Klebsiella pneumoniae were negative for mucoviscosity-associated gene A. Conclusion: There was evidence of the coexistence of bla- oxacillinase-48, bla-Verona integron-encoded metallo beta lactamase and bla-sulfhydryl variable genes in Klebsiella pneumoniae and Escherichia coli isolates from mixed urinary tract infection samples. Keywords: Carbapenemase, Klebsiella pneumoniae, Escherichia coli, Lactams